Experimental study on the external electrical thermal and dynamic power characteristics of alkaline water electrolyzer. (23rd April 2018) - Shen, Xiaojun; Zhang, Xiaoyun; Li, Guojie; Lie, Tek Tjing; Hong, Lv
Summary: As hydrogen production with a water electrolyzer is an effective way for renewable energy consumption, understanding the external electrical characteristics of water electrolyzer is of great significance for the modeling and simulation, system configuration, and control strategy of the system for hydrogen production by renewable energy. However, there are relatively fewer studies in this area. This paper presents the establishment of an experimental platform to conduct an experimental study on the static and dynamic voltage‐current characteristics and analyze the adjustability of the electric power of the traditional alkaline water electrolyzer, the relationship between the electrical characteristics and the electrolyte temperature, and operating point of the alkaline water electrolyzer. In addition, the mathematical fitting problem of the electrical characteristics of the alkaline water electrolyzer is discussed. The work could supply a reference to alkaline water electrolyzer intergrated application in renewable energy. Abstract : A test platform is set up to simultaneously acquire electrical characteristic signals of alkaline electrolyzer, and an experimental study of macroscopic electro‐thermal characteristics of electrolyzer is proposed. The law of the equivalent electrical impedance of the electrolyzer affected by electrolyte temperature is obtained by fitting the quantitative relationship between the equivalent electrical impedance and electrolyte temperature. The relationship between the static power and electrolyte temperature of electrolyzer is obtained, and the dynamic adjustment characteristics of electrolyzer power is given.